Difference in Effectiveness Gel Dosage form Green Papaya (Carica papaya L.) Skin Ethanol Extract and Gel Dosage form Green Papaya Seed Against Cutibacterium acnes Bacteria - Diana, Vivi Eulis; Abadi, Hafizhatul; Rumanti, Ruth Mayana; Andry, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Many things can cause acne, including stress, fatty foods, inappropriate or unsuitable makeup, and pollution. Cosmetics made from plants are safer to use. Papaya skin and seeds (Carica papaya L.) have antibacterial properties in the form of alkaloids, tannins, steroids, saponins, and flavonoids. This study aims to determine the comparison of the antibacterial power of young papaya skin ethanol extract gel and young papaya seed ethanol extract gel against Cutibacterium acnes bacteria. The research method is experimental with various formulas consisting of F0 (0%), F1 (11%), F2 (12%), and F3 (13%). The results of the study obtained antibacterial gel preparations from the three concentrations showed that the organoleptic test of the young papaya fruit skin ethanol extract gel preparation was light brown, blackish brown, dark blackish brown. The homogeneity test was homogeneous. The pH test was 5.9, 6.5, 7.0, and the seed ethanol extract gel preparation was light brown, dark brown, thick dark brown. The homogeneity test was homogeneous. Test pH 5.0, 5.6, 5.5, 5.1. The conclusion of this study is that the antibacterial effectiveness of young papaya fruit skin ethanol extract gel is greater than young papaya fruit seed ethanol extract gel at a concentration of 13% against Cutibacterium acnes bacteria.